Customer Satisfaction on Private Hospital Management Standards in Samarinda City - Radityo Suksmaneng Daru (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
This study analyzed customer satisfaction with the implementation of hospital management standards in several private hospitals. Customer satisfaction in the healthcare sector serves as a key indicator of service performance. Increasing competition among private hospitals in Samarinda requires the implementation of effective management standards to ensure high levels of patient satisfaction. The study employed a quantitative approach using a cross-sectional survey design. The sample consisted of 150 patients from three accredited private hospitals, selected purposively. The results indicate that staff competency and authority, facilities and safety management, quality improvement and patient safety, and medical information and records management significantly contribute to improved service outcomes, as indicated by p-values below 0.05. In contrast, hospital governance and infection prevention and control were not significant in influencing patient satisfaction. These findings underscore the central role of professional competence and operational support in enhancing service performance. The implementation of effective hospital management standards is closely associated with high levels of patient satisfaction. Hospitals should maintain and improve the quality of areas with lower performance. Future research is recommended to expand the variables and sample to achieve broader generalizability.